Physical Activity and Colorectal Cancer Prognosis According to Tumor-Infiltrating T Cells. Issue 4 (9th January 2019) - Koh, Hideo; Hamada, Tsuyoshi; Song, Mingyang; Liu, Li; Cao, Yin; Nowak, Jonathan A; da Silva, Annacarolina; Twombly, Tyler; Morikawa, Teppei; Kim, Sun A; Masugi, Yohei; Kosumi, Keisuke; et al.
Abstract: Background: Evidence suggests that high-level physical activity may potentially reduce cancer mortality through its immune enhancement effect. We therefore hypothesized that survival benefits associated with physical activity might be stronger in colorectal carcinomas with lower immune reaction at diagnosis. Methods: Using molecular pathological epidemiology databases of 470 colon and rectal carcinoma cases in the Nurses' Health Study and the Health Professionals Follow-up Study, we assessed the prognostic association of postdiagnosis physical activity in strata of densities of CD3 + cells, CD8 + cells, CD45RO (PTPRC) + cells, or FOXP3 + cells in tumor tissue. Cox proportional hazards regression model was used to adjust for potential confounders, including microsatellite instability, CpG island methylator phenotype, long interspersed nucleotide element-1 methylation, KRAS, BRAF, and PIK3CA mutations, and expression of CTNNB1 (beta-catenin), PTGS2 (cyclooxygenase-2), and IRS1 . Results: The association of postdiagnosis physical activity with colorectal cancer-specific mortality differed by CD3 + cell density ( P interaction < .001). Multivariable-adjusted colorectal cancer-specific mortality hazard ratios for a quartile-unit increase in physical activity were 0.56 (95% confidence interval = 0.38 to 0.83) among cases with the lowest quartile of CD3 + cell density compared with 1.14 (95% confidence interval = 0.79 to 1.65) in cases with the highest quartile. We observed no differential survival association of physical activity by densities of CD8 + cells, CD45RO + cells, or FOXP3 + cells. Conclusions: The association between postdiagnosis physical activity and colorectal cancer survival appeared stronger for carcinomas with lower T cell infiltrates, suggesting an interactive effect of exercise and immunity on colorectal cancer progression.